2021
DOI: 10.3390/bs11100135
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Female Breast Cancer Survivors Concerning Their Return to Work in Spain

Abstract: The objective of this study was to analyze the experiences of returning to work of women who had overcome breast cancer, identifying its physical and psychological consequences, the process they underwent, their motivations, and difficulties. A total of 19 female breast cancer survivors, with an age range of 30 to 57 years, participated in two focus groups. A semi-structured script was prepared about their experiences of returning to work. The results indicated that survivors’ self-perception was weakened by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Studies also reveal a significant association of physical, cognitive and psychological symptoms with impaired RTW and reduced level of work in a significant proportion of survivors of breast cancer [ 14 ]. Various studies [ 9 , 12 , 15 , 16 ] showed that women involved in physical work had decreased rates of RTW and difficulties adjusting to their work compared to non-manual workers. A systematic review of 26 studies [ 16 ] reported that sociodemographic factors like education and ethnicity, treatment-related factors such as side effects of chemotherapy, work-related factors like heavy physical work and disease-related factors like depression and emotional distress act as barriers to RTW in breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies also reveal a significant association of physical, cognitive and psychological symptoms with impaired RTW and reduced level of work in a significant proportion of survivors of breast cancer [ 14 ]. Various studies [ 9 , 12 , 15 , 16 ] showed that women involved in physical work had decreased rates of RTW and difficulties adjusting to their work compared to non-manual workers. A systematic review of 26 studies [ 16 ] reported that sociodemographic factors like education and ethnicity, treatment-related factors such as side effects of chemotherapy, work-related factors like heavy physical work and disease-related factors like depression and emotional distress act as barriers to RTW in breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported a significant prevalence of social stigma in breast cancer survivors [ 9 , 18 , 19 ]. This may vary among different countries depending on socio-cultural environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few previous studies have employed quantitative analysis to generate empirical data on the phenomena of work engagement among cancer survivors. In contrast, previous studies have relied mostly on qualitative approaches in exploring the experiences of cancer survivors in the workplace (Aguiar-Fernández et al, 2021 ; Torp et al, 2021 ). From a practical perspective, the study framework provides evidence to employers to shelve concerns about cancer survivors' capabilities, especially with regard to their work engagement.…”
Section: Implicationmentioning
confidence: 99%
“…Although several organizations or associations may be involved in the care of these patients, most of them do so on a voluntary rather than professional basis [ 15 ]. On the other hand, it should also be noted that one of the most pressing concerns for those patients who have overcome breast cancer is their successful return to work after treatment, taking into account their difficulties related to the physical appearance and, of much more importance for them, to their psychological and emotional problems [ 16 ].…”
Section: Introductionmentioning
confidence: 99%